Screw Dislocation Assisted Spontaneous Growth of HfB2 Tubes and Rods. Issue 7 (23rd April 2015) - Venugopal, Saranya; Jayaseelan, Daniel Doni; Paul, Anish; Vaidhyanathan, Bala; Binner, Jon G. P.; Brown, Peter M.; Fahrenholtz, W.
<x xml:space="preserve">Abstract</x> The mechanism of anisotropic growth of HfB2 rods has been discussed in this study. HfB2 powder has been synthesized via a sol–gel‐based route using phenolic resin, hafnium chloride, and boric acid as the source of carbon, hafnium, and boron respectively, though a small number of comparative experiments involved amorphous boron as the boron source. The effects of calcination dwell time and Hf:C and Hf:B molar ratio on the purity and morphology of the final powder have been studied and the mechanism of anisotropic growth of HfB2 has been investigated. It is hypothesized that imperfect oriented attachment of finer HfB2 particles results in screw dislocations in the coarser particles. The screw dislocation facilitates dislocation‐driven growth of particles into anisotropic HfB2 rods.